El ser afrocolombiano : rasgos de la cultura presentes en los programas etnoeducativos - Ramos Saavedra, Paula Andrea (Universidad de San Buenaventura - Cali, 2016)
This bibliographical research aims to determine the characteristics of the culture present in the ethnic education of the Afro-Colombian community programs, in order to give new meaning Afro-Colombian communities, as bearers of knowledge, experiences and cultural practices underlying social and spiritual meanings that give you music, art, literature, a central role in the future of Afro-Colombian peoples are expressed through cultural productions.